El lugar del arte en la opción por una desobediencia epistémica decolonial. - Bolaños, Martin (Hermenéutica, 2022)
The visualization of the ways of doing what is sensible in a globalized society is one more form of discipline of sensitivity and its poetics. The border between a colonized sensibility and an insurgent sensibility becomes blurred as the international distribution of the sensible assigns specific ways capable of domesticating the sensibilities that overwhelm it. Those sensitivities not that cannot be captured neither as merchandise, nor as an archive, nor as heritage. The overflow and excess of these sensitivities that have not been caught in the networks of an international art market jeopardize, by their very existence, the categories that aesthetics, as a modern-colonial discipline has produced to conceptualize and codify the sensitivities (isolationism) neutralized their capacities to witness historically subjugated life experiences. In this sense, decolonial stasis retrace the traced path, and one of the ways of retracing is to disarticulate or at least resignify words such as "art", "artist", "work", "production", "aesthetic", or "Poetic", among others.